Relationship of age-related hearing loss with cognitive decline and dementia in Sinitic tonal language-speaking populations: protocol for a systematic review and meta-analysis. Issue 4 (5th April 2022) - Fu, Xinxing; Liu, Bo; Wang, Shuo; Tian, Rong; Eikelboom, Robert H; Jayakody, Dona M P
Abstract : Introduction: Existing research on the potential association between age-related hearing loss (ARHL) and cognitive decline and dementia in tonal language-speaking populations is limited and inconsistent. There is psychophysiological evidence suggesting a tonal language background may be linked to enhanced general cognitive functions. We aim to systematically review the current evidence on the association between hearing loss and cognitive impairment/decline and dementia in older adults who speak a Sinitic tonal language, the most commonly spoken tonal language. Methods and analysis: This systematic review will consider peer-reviewed articles that employ objective or subjective hearing measurement and cognitive impairment or diagnosis of dementia. All relevant research publications in English or Chinese and published up to March 2022 will be considered for inclusion. Embase, MEDLINE, Web of Science, PsycINFO Google Scholar, SinoMed and Chinese Biomedical Database will be used, using both medical subject heading terms and keywords. The quality of evidence of an association between ARHL and cognitive impairment and/or dementia will be evaluated by the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system. A random-effects meta-analysis will be carried out with the Comprehensive Meta-Analysis software. Ethics and dissemination: Ethical approval will not be required for this systematic review. The results will be disseminated through peer-reviewed publications and conferences. PROSPERO registration number: CRD42021235310.